The Home Environment Interview and associations with energy balance behaviours and body weight in school-aged children - a feasibility, reliability, and validity study - Alice R. Kininmonth; Stephanie Schrempft; Andrea Smith; Louise Dye; Clare Lawton; Abigail Fisher; Clare Llewellyn; Alison Fildes (BMC, 2021)
Abstract Background The home environment is thought to influence children's weight trajectories. However, few studies utilise composite measures of the home environment to examine associations with energy balance behaviours and weight. The present study aimed to adapt and update a comprehensive measure of the obesogenic home environment previously developed for pre-schoolers, and explore associations with school-aged children's energy balance behaviours and weight. Methods Families from the Gemini cohort (n = 149) completed the Home Environment Interview (HEI) via telephone when their children were 12 years old. The HEI comprises four composite scores: one for each domain (food, activity and media) of the environment, as well as a score for the overall obesogenic home environment. The primary caregiver also reported each child's height and weight (using standard scales and height charts), diet, physical activity and sedentary screen-based behaviours. A test-retest sample (n = 20) of caregivers completed the HEI a second time, 7-14 days after the initial interview, to establish test-retest reliability. Results Children (n = 298) living in 'higher-risk' home environments (a 1 unit increase in the HEI obesogenic risk score) were less likely to consume fruits (OR; 95% CI = 0.40; 0.26-0.61, p < 0.001), and vegetables (0.30; 0.18-0.52, p < 0.001), and more likely to consume energy-dense snack foods (1.71; 1.08-2.69, p = 0.022), convenience foods (2.58; 1.64-4.05, p < 0.001), and fast foods (3.09; 1.90-5.04, p < 0.001). Children living in more obesogenic home environments also engaged in more screen-time (β (SE) = 4.55 (0.78), p < 0.001), spent more time playing video games (β (SE) = 1.56 (0.43), p < 0.001), and were less physically active (OR; 95% CI = 0.57; 0.40-0.80, p < 0.01). Additionally, there was a positive association between higher-risk overall home environment composite score and higher BMI-SDS (β (SE) = 0.23 (0.09), p < 0.01). This finding was mirrored for the home media composite (β (SE) = 0.12 (0.03), p < 0.001). The individual home food and activity composite scores were not associated with BMI-SDS. Conclusion Findings reveal associations between the overall obesogenic home environment and dietary intake, activity levels and screen-based sedentary behaviours, as well as BMI in 12 year olds. These findings suggest that the home environment, and in particular the home media environment, may be an important target for obesity prevention strategies.